Negative electrode lead paste of lead-acid storage battery and preparation method of negative electrode lead paste

By using lignin/graphene/nano-lead oxide nanocomposites as expansion agents in lead-acid batteries and using wet mixing-secondary dry mixing-spraying mixing, the problems of poor conductivity and insufficient lignin dispersion of lead-acid batteries are solved, and higher conductivity and dispersion are achieved.

CN120221599APending Publication Date: 2025-06-27JIESHOU HUAYU POWER SUPPLY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510375644.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-06-27

AI Technical Summary

Technical Problem

Lead-acid batteries using lignin as expansion agent have poor conductivity, and lignin has poor dispersion during the paste process.

Method used

The lignin/graphene/nanolead oxide nanocomposite is used as the expansion agent, and its dispersion is improved by wet mixing-secondary dry mixing-spray mixing.

Benefits of technology

The conductive properties of lead-acid batteries are significantly enhanced, the dispersion of lignin composite materials is improved, and the conductivity is synergistically improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120221599A_ABST
    Figure CN120221599A_ABST
Patent Text Reader

Abstract

The invention discloses lead-acid storage battery negative electrode lead paste and a preparation method thereof, and belongs to the technical field of lead-acid storage batteries. The negative electrode lead paste of the lead-acid storage battery comprises the following components in parts by weight: 100 parts of lead powder; 1-3 parts of acetylene black; 3-5 parts of a lignin / graphene / nano lead oxide nano composite material; 0.5 to 1.5 parts of humic acid; 0.3 to 0.8 part of short fiber; and 0.6-1 part of barium sulfate. According to the preparation method, the additive is firstly mixed with water to form the slurry, and then the slurry is mixed with the dry mixture in a spraying manner, so that the dispersity of the lignin in the lead paste is effectively improved, and meanwhile, a uniform conductive network and reaction active sites are provided for the lead paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lead-acid batteries, and particularly relates to a negative electrode lead paste for a lead-acid battery and a preparation method thereof. Background Art

[0002] At present, lead-acid batteries are widely used in the fields of automobiles, electric vehicles, communications, and power transmission due to their high safety, low cost, and recyclable raw materials. The low-temperature capacity of lead-acid batteries is a key performance index, but the poor low-temperature performance hinders the application of lead-acid batteries in the northern market. The low-temperature performance of lead-acid batteries mainly depends on the negative electrode plate. Since the negative electrode plate will shrink and passivate at low temperatures, adding an appropriate expanding agent to prevent the shrinkage and passivation of the negative electrode plate is one of the main solutions.

[0003] Lignosulfonate (hereinafter referred to as lignin) is a common type of organic expanding agent in lead-acid batteries. It has good dispersibility and is an anionic surfactant that can reduce the surface tension of water and change the properties of the electrode-solution interface. In the negative electrode of lead-acid batteries, lignin can effectively inhibit the surface shrinkage of the negative electrode active material during charge and discharge, which is beneficial to the preservation of the battery capacity during use. At the same time, a large number of studies have shown that lignin can also improve the low-temperature performance of the battery. Lignin is a derivative with a large variety, a complex structure, and an uncertain composition. However, through organic chemical analysis, it contains functional groups such as hydroxyl -OH and carbonyl -C=O. When the battery is formed, due to the increase in battery temperature and the decrease in the pH value of the electrolyte, a large amount of lignin dissolves into the positive electrode of the battery and is oxidized and decomposed during the subsequent charging process, resulting in the gradual disappearance of its function and the decline of battery performance. Summary of the Invention

[0004] One of the purposes of the present invention is to provide a negative electrode lead paste for a lead-acid battery to solve the problem of poor electrical conductivity of lead-acid batteries using lignin as an expanding agent;

[0005] Another purpose of the present invention is to provide a preparation method for a negative electrode lead paste for a lead-acid battery to solve the problem of poor dispersibility of lignin during the paste mixing process.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] In the first aspect, the present invention provides a negative electrode lead paste for a lead-acid battery, which includes the following components by weight:

[0008] 100 parts of lead powder; 1 - 3 parts of acetylene black; 3 - 5 parts of lignin / graphene / nano lead oxide nanocomposite; 0.5 - 1.5 parts of humic acid; 0.3 - 0.8 parts of short fiber; 0.6 - 1 part of barium sulfate.

[0009] As a further solution of the present invention, the lignin / graphene / lead oxide nanocomposite is prepared by the following steps:

[0010] Step 1: Add lignin to a sodium sulfite solution, stir and react at 80-90 °C for 5-8 h, then neutralize, precipitate, wash and collect sulfonated lignin, and disperse it in a sodium hydroxide solution to form a homogeneous solution 1;

[0011] Step 2: Disperse graphene powder in deionized water, ultrasonically disperse it evenly to obtain a graphene dispersion, then add the homogeneous solution 1, and ultrasonically disperse and react for 1-2 h to obtain a composite solution 2;

[0012] Step 3: Under stirring conditions, add sodium dodecylbenzenesulfonate to a lead nitrate solution, mix evenly, then add it to the composite solution 2, and continue stirring to obtain a mixed solution 3; add a sodium bicarbonate solution to the mixed solution 3, and carry out hydrothermal ultrasonic reaction at 60-80 °C for 1-3 h, then collect the product;

[0013] Step 4: Place the product in a protective atmosphere for calcination treatment to obtain a lignin / graphene / lead oxide composite material.

[0014] Further, in Step 1, the mass percentage of the sodium sulfite solution is 8%-15%, and the mass ratio of lignin to sodium sulfite is 1:4.

[0015] Further, in Step 1, the concentration of the sodium hydroxide solution is 0.2-0.4 mol / L; the dosage ratio of sulfonated lignin to the sodium hydroxide solution is 1-2 g:100 mL.

[0016] Further, in Step 2, the concentration of the graphene dispersion is 0.4-0.8 g / 100 mL.

[0017] Further, in Step 2, the volume ratio of the graphene dispersion to the homogeneous solution 1 is 1:1.

[0018] Further, in Step 3, the dosage ratio of lead nitrate, sodium dodecylbenzenesulfonate and graphene in the composite solution 2 is 1 g:1 g:1 g.

[0019] Further, in Step 3, the concentration of the sodium bicarbonate solution is 0.5-0.8 mol / L; the volume ratio of the sodium bicarbonate solution to the lead nitrate solution is 1:2.

[0020] Further, in Step 4, the protective atmosphere is nitrogen.

[0021] Further, in Step 4, the calcination treatment is specifically to uniformly heat up to 200-400 °C at a rate of 6-8 °C / min and keep the temperature for calcination for 2-4 h.

[0022] Second aspect, a method for preparing the negative electrode lead paste of a lead-acid battery, comprising the following steps:

[0023] S1. Add acetylene black, lignin / graphene / nano lead oxide nanocomposite, and humic acid to pure water in sequence, control the temperature ≤ 40 °C, stir and mix evenly, and perform ultrasonic dispersion to obtain slurry A;

[0024] S2. Add 50% of the total amount of lead powder to the paste mixer. During the stirring process, add short fibers and barium sulfate in sequence, then add the remaining lead powder, and continue to mix evenly by dry mixing to obtain material B;

[0025] S3. Use a spraying device to evenly spray slurry A into the paste mixer, and synchronously stir and mix it with material B;

[0026] S4. After the feeding is completed, add pure water to make the humidity of the material 12% - 15%, continue to stir for 10 - 20 min, then add sulfuric acid to adjust the pH to 3.5 - 4.5, and continue to stir for 10 - 15 min to obtain the negative electrode lead paste of the lead-acid battery with a density of 4.2 - 4.5 g / cm 3 ³.

[0027] As a further solution of the present invention, in S1, the solid content of slurry A is 20% - 30%.

[0028] As a further solution of the present invention, in S3, the spraying speed is 6 - 9 mL / min.

[0029] As a further solution of the present invention, in S4, the concentration of sulfuric acid is 5% - 10%.

[0030] As a further solution of the present invention, the stirring speed is 200 - 400 rpm.

[0031] Compared with the prior art, the beneficial effects of the present invention are:

[0032] 1. The present invention provides a negative electrode lead paste of a lead-acid battery. In its preparation method, by first mixing the additive with water to form a slurry and then mixing it with the dry mixture by spraying, the dispersion of lignin in the lead paste is effectively improved, and at the same time, a uniform conductive network and reaction active sites are provided for the lead paste.

[0033] 2. In the process of preparing the lignin / graphene / lead oxide nanocomposite of the present invention, lignin is added to the sodium sulfite solution. Through the reduction of sodium sulfite, the hydroxyl group (-OH) in the lignin molecule is sulfonated into a sulfonic acid group (-SO3H). The sulfonated lignin has higher polarity and hydrophilicity, and can better combine with other components. The introduction of the sulfonation group improves the chemical stability of lignin and makes it not easily decomposed in subsequent reactions. The sulfonated lignin solution is slowly added to the graphene dispersion liquid. Under the action of ultrasonic waves, the composite is achieved by using hydrogen bonds and π-π interactions; sodium dodecylbenzenesulfonate is used as a surfactant to stabilize the lead ions in the lead nitrate solution and prevent them from precipitating. A sodium bicarbonate solution is added under hydrothermal ultrasonic conditions. The carbonate ions generated by the decomposition of sodium bicarbonate react with the lead ions to form lead oxide nanoparticles uniformly loaded in the three-dimensional structure of lignin; through calcination, the chemical bonding between lead oxide, graphene and lignin is further promoted. Through the synergistic effect of lead oxide and graphene, the phenomenon that a large amount of lignin dissolves and decomposes due to the increase in battery temperature and the decrease in the pH value of the electrolyte during the battery formation process is avoided. The prepared composite material has higher electrical conductivity, thermal stability and mechanical strength. Brief Description of the Drawings

[0034] The present invention will be further described below in conjunction with the drawings.

[0035] Figure 1 It is a schematic diagram of the preparation process flow of the lignin / graphene / lead oxide nanocomposite of the present invention. Detailed Embodiments

[0036] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0037] Obviously, the following description is only some examples or embodiments of the present application. For those of ordinary skill in the art, without creative efforts, the present application can also be applied to other similar scenarios. In addition, it can also be understood that although the efforts made in this development process may be complex and lengthy, for those of ordinary skill in the art related to the content disclosed in the present application, some design, manufacturing or production changes based on the technical content disclosed in the present application are only conventional technical means and should not be understood as the content disclosed in the present application is insufficient.

[0038] However, there may be cases where unnecessary details are omitted. For example, details of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to prevent the following descriptions from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following descriptions are provided for those skilled in the art to fully understand this application and are not intended to limit the subject matter recited in the claims.

[0039] If there is no special instruction, all embodiments and optional embodiments of this application can be combined with each other to form new technical solutions, and all technical features and optional technical features of this application can be combined with each other to form new technical solutions.

[0040] Preparation Example 1

[0041] Please refer to Figure 1 , a lignin / graphene / lead nanooxide nanocomposite, which is prepared by the following steps:

[0042] Lignin: 2 g;

[0043] Sodium sulfite: 8 g, configured into an 80 mL sodium sulfite solution with a mass percentage of 10%;

[0044] Sodium hydroxide solution: 0.3 mol / L, 200 mL;

[0045] Graphene: 1.2 g, configured into a graphene dispersion with a concentration of 1.2 g / 200 mL;

[0046] Lead nitrate: 1.2 g, configured into an 18 mL, 0.2 mol / L lead nitrate solution;

[0047] Sodium dodecylbenzenesulfonate: 1.2 g;

[0048] Sodium hydroxide solution: 0.6 mol / L, 9 mL;

[0049] Step 1: Add 2 g of lignin to an 80 mL sodium sulfite solution with a mass percentage of 10%, stir and react at 85°C for 7 h, then collect sulfonated lignin through neutralization, precipitation, and washing. Take 3 g of sulfonated lignin and disperse it in 200 mL of a 0.3 mol / L sodium hydroxide solution to form homogeneous solution 1;

[0050] Step 2: Disperse 1.2 g of graphene powder in 200 mL of deionized water, ultrasonically disperse it evenly to obtain a graphene dispersion, then add homogeneous solution 1 and ultrasonically disperse and react for 1.5 h to obtain composite solution 2;

[0051] Step 3: Under the stirring condition of 300 rpm, add 1.2 g of sodium dodecylbenzenesulfonate to 18 mL of 0.2 mol / L lead nitrate solution. After mixing evenly, add it to the composite solution 2, and continue stirring to obtain the mixed solution 3; add 9 mL of 0.6 mol / L sodium bicarbonate solution to the mixed solution 3. After hydrothermal ultrasonic reaction at 70 °C for 2 h, collect the product;

[0052] Step 4: Place the product in a nitrogen atmosphere for calcination treatment, heat it up to 350 °C at a constant rate of 7 °C / min, and keep it calcined for 2.5 h to obtain the lignin / graphene / lead oxide nanocomposite.

[0053] Preparation Example 2

[0054] A lignin / graphene / lead oxide nanocomposite is prepared by the following steps:

[0055] Lignin: 2 g;

[0056] Sodium sulfite: 8 g, configured into a 54 mL sodium sulfite solution with a mass percentage of 15%;

[0057] Sodium hydroxide solution: 0.3 mol / L, 200 mL;

[0058] Graphene: 0.8 g, configured into a graphene dispersion with a concentration of 0.8 g / 200 mL;

[0059] Lead nitrate: 0.8 g, configured into 12 mL of 0.2 mol / L lead nitrate solution;

[0060] Sodium dodecylbenzenesulfonate: 0.8 g;

[0061] Sodium hydroxide solution: 0.6 mol / L, 6 mL;

[0062] Step 1: Add 2 g of lignin to 54 mL of sodium sulfite solution with a mass percentage of 15%. After stirring and reacting at 85 °C for 7 h, neutralize, precipitate, and wash to collect sulfonated lignin. Take 3 g of sulfonated lignin and disperse it in 200 mL of 0.3 mol / L sodium hydroxide solution to form a homogeneous solution 1;

[0063] Step 2: Disperse 0.8 g of graphene powder in 200 mL of deionized water, ultrasonically disperse it evenly to obtain a graphene dispersion, and then add the homogeneous solution 1, and ultrasonically disperse and react for 1.5 h to obtain a composite solution 2;

[0064] Step 3: Under the stirring condition of 300 rpm, add 0.8 g of sodium dodecylbenzenesulfonate to 12 mL of 0.2 mol / L lead nitrate solution. After mixing evenly, add it to the composite solution 2, and continue stirring to obtain the mixed solution 3. Add 6 mL of 0.6 mol / L sodium bicarbonate solution to the mixed solution 3. After hydrothermal ultrasonic reaction at 70 °C for 2 h, collect the product.

[0065] Step 4: Place the product in a nitrogen atmosphere for calcination treatment. Heat it up to 350 °C at a constant rate of 7 °C / min, and keep it calcined for 2.5 h to obtain the lignin / graphene / lead oxide nanocomposite.

[0066] Preparation Example 3

[0067] A lignin / graphene / lead oxide nanocomposite is prepared by the following steps:

[0068] Lignin: 2 g;

[0069] Sodium sulfite: 8 g, configured into 100 mL of sodium sulfite solution with a mass percentage of 8%;

[0070] Sodium hydroxide solution: 0.3 mol / L, 200 mL;

[0071] Graphene: 1.6 g, configured into a graphene dispersion with a concentration of 1.6 g / 200 mL;

[0072] Lead nitrate: 1.6 g, configured into 24 mL of 0.2 mol / L lead nitrate solution;

[0073] Sodium dodecylbenzenesulfonate: 1.6 g;

[0074] Sodium hydroxide solution: 0.6 mol / L, 12 mL;

[0075] Step 1: Add 2 g of lignin to 100 mL of sodium sulfite solution with a mass percentage of 8%. Stir and react at 85 °C for 7 h, then neutralize, precipitate, wash and collect the sulfonated lignin. Take 3 g of sulfonated lignin and disperse it in 200 mL of 0.3 mol / L sodium hydroxide solution to form a homogeneous solution 1.

[0076] Step 2: Disperse 1.6 g of graphene powder in 200 mL of deionized water, ultrasonically disperse it evenly to obtain a graphene dispersion, and then add it to the homogeneous solution 1 and ultrasonically disperse and react for 1.5 h to obtain the composite solution 2.

[0077] Step 3: Under the stirring condition of 300 rpm, add 1.6 g of sodium dodecylbenzenesulfonate to 24 mL of 0.2 mol / L lead nitrate solution. After mixing evenly, add it to Composite Solution 2, and continue stirring to obtain Mixed Solution 3; add 12 mL of 0.6 mol / L sodium bicarbonate solution to Mixed Solution 3. After hydrothermal ultrasonic reaction at 70 °C for 2 h, collect the product;

[0078] Step 4: Place the product in a nitrogen atmosphere for calcination treatment. Heat it up to 350 °C at a constant rate of 7 °C / min, and keep it calcined for 2.5 h to obtain the lignin / graphene / nano lead oxide composite material.

[0079] Example 1

[0080] A negative electrode lead paste for lead-acid batteries, by weight, comprises the following components:

[0081] 100 parts of lead powder; 2 parts of acetylene black; 4 parts of lignin / graphene / nano lead oxide nanocomposite material (prepared in Preparation Example 1); 1 part of humic acid; 0.5 part of short fiber; 0.8 part of barium sulfate;

[0082] The preparation method of the negative electrode lead paste for lead-acid batteries comprises the following steps:

[0083] S1. Add acetylene black, the lignin / graphene / nano lead oxide nanocomposite material prepared in Preparation Example 1, and humic acid to pure water in sequence, control the temperature ≤ 40 °C, stir and mix evenly at a rotation speed of 300 rpm, and ultrasonically disperse for 30 min to obtain Slurry A with a solid content of 25%;

[0084] S2. Add 50% of the total amount of lead powder to the paste mixer. During the stirring process, add short fiber and barium sulfate in sequence, then add the remaining lead powder, and continue to mix evenly by dry mixing to obtain Material B;

[0085] S3. Use a spraying device to evenly spray Slurry A into the paste mixer at a rate of 8 mL / min, and synchronously stir and mix with Material B;

[0086] S4. After adding materials, add pure water to make the humidity of the material reach 14%, continue to stir for 20 min, then add 8% sulfuric acid to adjust the pH to 4 ± 0.2, and continue to stir for 12 min to obtain the negative electrode lead paste for lead-acid batteries with a density of 4.3 g / cm 3 of.

[0087] Example 2

[0088] A negative electrode lead paste for lead-acid batteries, which is different from Example 1 in that the lignin / graphene / nano lead oxide nanocomposite material is prepared in Preparation Example 2, and the other components and parameters remain the same.

[0089] Example 3

[0090] A negative lead paste for lead-acid batteries, which is different from that in Example 1 in that the lignin / graphene / nano-lead oxide nanocomposite is prepared by Preparation Example 3, and the other components and parameters remain the same.

[0091] Example 4

[0092] A negative lead paste for lead-acid batteries, which is different from that in Example 1 in that the weight fraction of the lignin / graphene / nano-lead oxide nanocomposite is 3 parts, and the other components and parameters remain the same.

[0093] Example 5

[0094] A negative lead paste for lead-acid batteries, which is different from that in Example 1 in that the weight fraction of the lignin / graphene / nano-lead oxide nanocomposite is 5 parts, and the other components and parameters remain the same.

[0095] Comparative Example 1

[0096] A negative lead paste for lead-acid batteries, which is different from that in Example 1 in that the lignin / graphene / nano-lead oxide nanocomposite is replaced by lignin, and the other components and parameters remain the same.

[0097] Comparative Example 2

[0098] A negative lead paste for lead-acid batteries, which is different from that in Example 1 in that the lignin / graphene / nano-lead oxide nanocomposite is replaced by a lignin-graphene hybrid material obtained by mixing lignin and graphene in a weight ratio of 2.5:1, and the other components and parameters remain the same.

[0099] Comparative Example 3

[0100] A negative lead paste for lead-acid batteries, which is different from that in Example 1 in that the lignin / graphene / nano-lead oxide nanocomposite is replaced by a lignin-graphene-lead oxide hybrid material obtained by mixing lignin, graphene, and lead oxide in a weight ratio of 2.5:1:1, and the other components and parameters remain the same.

[0101] Comparative Example 4

[0102] A negative lead paste for lead-acid batteries, by weight, comprises the following components:

[0103] 100 parts of lead powder; 2 parts of acetylene black; 4 parts of lignin / graphene / nano-lead oxide nanocomposite (prepared by Preparation Example 1); 1 part of humic acid; 0.5 part of short fiber; 0.8 part of barium sulfate;

[0104] The preparation method of the negative lead paste for lead-acid batteries comprises the following steps:

[0105] Add acetylene black, the lignin / graphene / nano lead oxide nanocomposite prepared in Preparation Example 1, humic acid, lead powder, short fibers, and barium sulfate into the paste mixer in sequence. Control the temperature ≤ 40°C, and add pure water under the stirring condition of 300 rpm until the material humidity reaches 14%. After continuing to stir for 50 min, add 8% sulfuric acid to adjust the pH to 4 ± 0.2, and continue to stir for 12 min to obtain a lead-acid battery negative electrode lead paste with a density of 4.3 g / cm 3 of the lead-acid battery negative electrode lead paste.

[0106] Perform performance tests on the lead-acid battery negative electrode lead pastes prepared in Examples 1-5 and Comparative Examples 1-4:

[0107] Prepare the lead-acid battery negative electrode plates from the lead-acid battery negative electrode lead pastes prepared in Examples 1-5 and Comparative Examples 1-4 through the processes of smearing, curing, and drying, assemble them into 6-DZF-20 type experimental batteries, and conduct normal temperature capacity, cycle life, and low-temperature high-current discharge tests with reference to the battery national standard GB / T 22199-2017. The test results are shown in Table 1.

[0108] Table 1

[0109]

[0110] It can be seen from Table 1 that adding the lignin / graphene / nano lead oxide nanocomposite to the lead-acid battery negative electrode lead paste of the present invention can significantly enhance the conductivity of the lead-acid battery. In addition, due to the wet mixing - secondary dry mixing - spraying mixing method adopted in its preparation method, the dispersibility of the lignin composite can be further improved, thereby synergistically improving the conductivity.

[0111] It should be noted that in this article, relational terms such as first and second are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements not only includes those elements, but also includes other elements not expressly listed, or also includes elements inherent to such process, method, article or device.

[0112] Although the embodiments of the present invention have been shown and described, for those of ordinary skill in the art, it can be understood that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A lead paste for negative electrode of a lead-acid battery, characterized in that: According to parts by weight, it includes the following components: 100 parts of lead powder; 1-3 parts of acetylene black; 3-5 parts of lignin / graphene / nano-lead oxide nanocomposite material; 0.5-1.5 parts of humic acid; 0.3-0.8 parts of short fibers; and 0.6-1 parts of barium sulfate.

2. A lead paste for negative electrode of a lead-acid battery according to claim 1, characterized in that: The lignin / graphene / nano lead oxide nanocomposite material is prepared by the following steps: Step 1: adding lignin to a sodium sulfite solution, stirring and reacting at 80-90° C. for 5-8 hours, neutralizing, precipitating, washing, collecting sulfonated lignin, and dispersing it in a sodium hydroxide solution to form a homogeneous solution 1; Step 2: dispersing graphene powder in deionized water, and uniformly dispersing by ultrasonication to obtain a graphene dispersion, and then adding the homogeneous solution 1, and ultrasonically dispersing the reaction for 1-2 hours to obtain a composite solution 2; Step 3: under stirring conditions, adding sodium dodecylbenzene sulfonate to the lead nitrate solution, mixing evenly, adding to the composite solution 2, and continuing to stir to obtain a mixed solution 3; adding sodium bicarbonate solution to the mixed solution 3, and performing hydrothermal ultrasonic reaction at 60-80° C. for 1-3 hours, and collecting the product; Step 4: placing the product in a protective atmosphere for calcination to obtain a lignin / graphene / nano lead oxide composite material.

3. A lead paste for negative electrode of a lead-acid battery according to claim 2, characterized in that: In step 1, the mass percentage of the sodium sulfite solution is 8%-15%, and the mass ratio of lignin to sodium sulfite is 1:

4.

4. A lead paste for negative electrode of a lead-acid battery according to claim 2, characterized in that: In step 1, the concentration of the sodium hydroxide solution is 0.2-0.4 mol / L; the usage ratio of sulfonated lignin to the sodium hydroxide solution is 1-2 g:100 mL.

5. The negative electrode lead paste for lead-acid batteries according to claim 2, characterized in that: In step 2, the concentration of the graphene dispersion is 0.4-0.8 g / 100 mL.

6. A lead paste for negative electrode of a lead-acid battery according to claim 2, characterized in that: In step 2, the volume ratio of the graphene dispersion to the homogeneous solution 1 is 1:

1.

7. A lead paste for negative electrode of a lead-acid battery according to claim 2, characterized in that: In step 3, the usage ratio of lead nitrate, sodium dodecylbenzene sulfonate and graphene in the composite solution 2 is 1g:1g:1g.

8. The negative electrode lead paste for lead-acid batteries according to claim 2, characterized in that: In step 3, the concentration of the sodium bicarbonate solution is 0.5-0.8 mol / L; the volume ratio of the sodium bicarbonate solution to the lead nitrate solution is 1:

2.

9. A method for preparing a negative electrode lead paste for a lead-acid battery as claimed in claim 1, characterized in that: The following steps are involved: S1. Add acetylene black, lignin / graphene / nano-lead oxide nanocomposite material and humic acid into pure water in sequence, control the temperature to ≤40°C, stir and mix evenly, and ultrasonically disperse to obtain slurry A; S2. Add 50% of the total lead powder to the paste machine, add short fibers and barium sulfate in turn during the stirring process, then add the remaining lead powder, continue dry mixing to obtain material B; S3. Use a spraying device to evenly spray slurry A into the paste machine and stir and mix with material B simultaneously; S4. After the addition is completed, add pure water until the material humidity is 12%-15%, continue stirring for 10-20 minutes, add sulfuric acid to adjust the pH to 3.5-4.5, continue stirring for 10-15 minutes to obtain a density of 4.2-4.5g / cm 3 Lead paste for negative electrode of lead-acid battery.

10. The method for preparing a negative electrode lead paste for a lead-acid battery according to claim 9, characterized in that: In S1, the solid content of slurry A is 20%-30%.